Genetic Testing of Maturity-Onset Diabetes of the Young Current Status and Future Perspectives - Firdous, Parveena; Nissar, Kamran; Ali, Sajad; Ganai, Bashir Ahmad; Shabir, Uzma; Hassan, Toyeeba; Masoodi, Shariq Rashid (Frontiers in Endocrinology, 2018)
Diabetes is a global epidemic problem growing exponentially in Asian countries posing a serious threat. Among diabetes, maturity onset diabetes of the young (MODY) is a heterogeneous group of monogenic disorders that occurs due to β cell dysfunction. Genetic defects in the pancreatic β-cells result in the decrease of insulin production required for glucose utilization thereby lead to early onset diabetes (often < 25 years). It is generally considered as non-insulin dependent form of diabetes and comprises of 1-5% of total diabetes. Till date, fourteen genes have been identified and mutation in them may lead to MODY. Different genetic testing methodologies like linkage analysis, restriction fragment length polymorphism (RFLP) and DNA sequencing are used for the accurate and correct investigation of gene mutations associated with MODY. The next generation sequencing has emerged as one of the most promising and effective tools to identify novel mutated genes related to MODY. Diagnosis of MODY is mainly relying on the sequential screening of the three marker genes like hepatocyte nuclear factor 1 alpha (HNF1α), hepatocyte nuclear factor 4 alpha (HNF4α) and Glucokinase (GCK). Interestingly, MODY patients can be managed by diet alone for many years and may also require minimal doses of sulfonylureas. The primary objective of this article is to provide a review on current status of MODY, its prevalence, genetic testing/ diagnosis, possible treatment and future perspective.